A study on 2 dimensional 2 Dot 1 Electron quantum dot cellular automata based reversible 2:1 MUX design: an energy analytical approach. Issue 2 (2nd July 2016) - Ghosh, Mili; Mukhopadhyay, Debarka; Dutta, Paramartha
Abstract : In nanoscale, quantum dot cellular automata (QCA) is one of the most trusted, discussed alternatives which can efficiently replace the CMOS technology. The current article presents the design methodology of reversible 2:1 multiplexer with the help of 2 Dot 1 Electron QCA and presents some formalism regarding the energy optimization of 2 Dot 1 Electron QCA circuits which is applicable to any such circuit. The first formalism estimates the internal energy of electron within QCA cells, whereas the next one estimates the minimum energy requirement to execute any such QCA circuit efficiently. It is established that for any 2 Dot 1 Electron QCA architecture, factors affecting energy computation mostly are the electron quantum number ( n ) and the intermediate electron quantum number lying between 1 and . The incident energy frequency is found directly related to N (the number of total cells in the architecture) and quadratic function of n and, whereas the frequency of dissipated energy is directly related to N and . The frequency of differential energy is directly proportional to N and quadratic function of . Moreover, the relaxation time is inversely proportional to N as well as to .